The Role of Palliative Care in Reducing Symptoms and Improving Quality of Life for Patients with Idiopathic Pulmonary Fibrosis: A Review - Richard H. Zou; Daniel J. Kass; Kevin F. Gibson; Kathleen O. Lindell (Pulmonary Therapy, 2020)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with a median survival of 3–4 years from time of initial diagnosis, similar to the time course of many malignancies. A hallmark of IPF is its unpredictable disease course, ranging from long periods of clinical stability to acute exacerbations with rapid decompensation. As the disease progresses, patients with chronic cough and progressive exertional dyspnea become oxygen dependent. They may experience significant distress due to concurrent depression, anxiety, and fatigue, which often lead to increased symptom burden and decreased quality of life. Despite these complications, palliative care is an underutilized, and often underappreciated, resource before end-of-life care in this population. While there is growing recognition about early palliative care in IPF, current data suggest referral patterns vary widely based on institutional practices. In addition to focusing on symptom management, there is emphasis on supplemental oxygen use, pulmonary rehabilitation, quality of life, and end-of-life care. Importantly, increased use of support groups and national foundation forums have served as venues for further disease education, communication, and advanced care planning outside of the hospital settings. The purpose of this review article is to discuss the clinical features of IPF, the role of palliative care in chronic disease management, current data supporting benefits of palliative care in IPF, its role in symptom management, and practices to help patients and their caregivers achieve their best quality of life.